Efficacy Of Sex Education On Academic Depression Behaviour Of Schooling Adolescents With Special Needs In Nsukka Education Zone Of Enugu State, Nigeria - Ugwoezuonu, A.U.; C. Ncheke, Damian; Omeje, Grace Ngozi; Okafor, Henrietta Ifeoma; Anthony, Ofozoba Chinonso; Ozoemena, Lilian Chijioke; Patience, Nwobodo; Ezeunara, D. C.; Agodo, Theresa Chima; Awoke, Ngozi Ngwanma; et al. (Journal of Neonatal Surgery, 2025)
This paper assessed the efficacy of sex education on academic depression behavior of schooling adolescents with special needs. Pre-test posttest randomized control trial experimental design was adopted by the researchers for the study. Fifty two (52) schooling adolescents who were drawn through proportionate stratified random sampling technique constituted the sample for the study. The school adolescents with special needs were randomly assigned to experimental (30) and control (22) groups. Depression Assessment Scale for Schooling Adolescents with Special Needs (DASSASN) and Academic Depression Behaviour Scale for Schooling Adolescents with Special Needs (ADBSSASN) were used for data collection. DASSASN and ADBSSASN were duly validated by experts in test development and the internal consistency reliability index of the items estimated as 0.78 and 0.77 respectively using Cronbach alpha method. Before the commencement of the testing and treatment programme, the researchers assured the participants of confidentiality of interactions and personal information as they work to get her in self-disclosure. After that, pretreatment assessment (pre-test) was conducted using the DASSASN and ADBSSASN in order to collect baseline data (Time 1). After that the experimental group was exposed to 90 minutes of the sex education (SE) programme twice a week for a period of 6 weeks. The treatment took place May and June, 2024. Post-test (Time 2) assessment was conducted one week after the last treatment session. Besides, a follow-up assessment was conducted after two months of the treatment (Time 3). Data collected were analyzed using repeated measures analysis of variance. The findings of the study revealed that the efficacy of sex education on the reduction of depression behavior among schooling adolescents with special needs was significant at post-test and follow-up measures. One of the implications of the findings is that if schooling adolescents with special needs are not properly counseled, their depression behavior will continue to increase. Based on the findings, it was recommended among others that Federal Government or relevant authorities should provide enough guidance counselors in the various institutions of higher learning who will assist in the counselling of schooling adolescents with special needs on dangers of depression using sex education.